SYSTEMATIC LITERATURE REVIEW: PROBLEM BASED LEARNING MODEL FOR MATHEMATICAL CONCEPT COMPREHENSION ABILITY - Hulwani, Almas Zati; Nindiasari, Hepsi (Program Studi Magister Pendidikan Matematika, Universitas Siliwangi, 2025)
This study aims to analyze the misconceptions experienced by grade XI-4 students at SMAN 1 Pasuruan in understanding matrix concepts, including operations such as multiplication, determinants, minors, cofactors, and matrix equations. The study employed a qualitative descriptive method, collecting data through tests and analyzing students’ responses. The findings revealed two primary types of misconceptions: notation and generalization. Notation misconceptions involved errors in using symbols, such as replacing vertical brackets with regular brackets for minors and cofactors or misapplying the positive and negative sign patterns in cofactor elements. Generalization misconceptions occurred when students misunderstood the rules of matrix multiplication, such as assuming the resulting order of multiplication follows the first matrix or incorrectly applying procedural steps to determine adjoints and inverses. The study recommends teaching approaches that emphasize conceptual understanding and the application of problem-based strategies. Varied practice questions and in-depth explanations linking procedural steps to foundational concepts are expected to improve students’ comprehension. These findings contribute to the development of effective mathematics teaching strategies to minimize misconceptions in matrix topics in the future.